A Distributed Algorithm For Monitoring An Expanding Hole In Wireless Sensor Networks (Informatica, 2016)
Holes in sensor networks are regions that have no operating nodes and that may occur due to several reasons, including cases caused by natural obstacles or disaster suffered areas. Determining the location and shape of holes can help to monitor these disasters (such as volcano, tsunami, etc.) or help to make smart, early routing decisions for circumventing a hole. There are many hole determination algorithms proposed in the literature, however, these only consider the networks with static holes i.e. with stable boundary nodes. Moreover, most of these are designed in a centralized manner which is not suitable to the unstable situation of networks with an expanding hole. In this paper, we propose an algorithmic scheme not only for determining the initial shape but also for monitoring and quickly reporting about the area of a hole gradually expanding. Our algorithms are designed in a distributed manner and our initial simulation results show that our protocol is lightweight and feasible with monitoring sensor networks with an expanding hole.